RISK FACTORS FOR BREAST CANCER INCIDENCE IN THE MALANG CITY HOSPITAL AREA - Wulandari, Lisa Purbawaning; Triningsih, Reni Wahyu; Aryani, Hening Ryan (Indonesian Journal of Health Science, 2025)
The world is facing a health problem where there is an epidemiological shift, namely the emergence of infectious diseases into non-infectious diseases. One of the non-infectious diseases that is a global health burden is cancer. The exact cause of breast cancer is still unknown. However, many factors are thought to influence the high incidence of breast cancer. The purpose of this study was to determine the risk factors for breast cancer in Hospitals in the Malang City Area. Quantitative descriptive research with a secondary data analysis strategy was conducted on all patients diagnosed with breast cancer in 4 major hospitals in Malang City in January - December 2023, with a total of 1464 data using the total sampling technique. The data was processed using descriptive statistical methods. The results showed that the majority of women diagnosed with breast cancer were over 50 years old (58.1%), and married (86.95%). A total of 67.96% of respondents were multiparous mothers, 31.69% used 3-month hormonal contraceptive injections, and some had a medical history of hypertension (7.31%). This study shows the importance of early detection of breast cancer at all ages and equitable access to health facilities that provide cancer care services.